MODEL DEVELOPMENT OF CREATIVE DRAWING TRAINING MANAGEMENT WITH THE TOPIC OF CONSERVATION FOR KINDERGARTEN TEACHERS IN SEMARANG - Budi Utomo, Kamsidjo (The Journal of Educational Development, 2014)
Training is an effective way to professionally improve teachersâ human resource. The purpose of this training was to prepare professional kindergarten teachers to make creative drawing to children golden age. Teachers have significant roles in their "Golden age of Drawing" due to the tendency of children to imitate adultsâ / Kindergarten Teachersâ behaviors. Professionally kindergarten teachers supposed to be competence in creative drawing that stimulating the spirit of child draw, is the availability of creative drawing training model and should be professionally conducted due to the principles of measured training management that ideal kindergarten teachers who are professional and having competitiveness will be realized in the performance of their duties as educational practitioners. Research and Development should be conducted for the innovations of training model management. The results of preliminary study showed that existing training model of drawing had not been professionally taken care since the principles of fine management had not been well conducted, such as planning, organization, implementation, evaluation, and further follow-up.